PREPOSISI BAHASA INGGRIS DAN BAHASA MELAYU MANADO - LUMIWU, OCHELIA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2017)
ABSTRACT This research is entitled ‘Preposition in English and in Manadonese Malay (A Contrastive analysis). The objects of the research are to identify, classify, analised, and described the forms and meanings of preposition in English and in Manadonese Malay language, and to find out the similarities and differences. The English data were taken from some grammatical books and journals of English teaching forum while the data in Manadonese Malay language have been collected by interviewing some informants. This research used descriptive method. The writer used the concept Crystal (1999), Arts and Arts (1982), Harman (1992), and Lado (1979). It is found that the prepositions in English and Manadonese Malay have similarities and differences. The similarities can be found in their forms and meanings. Both languages have simple and complex preposition which is indicating cause or reasons, condition, direction, instrument, manner, participation, place, purpose, source, and time. The differences are shown in the forms. While English language has fourteen complex forms of preposition Manadonese Malay language only has one complex forms of preposition. Keywords: Prepositions, English and Manadonese Malay, Contrastive Analysis